Inklusi Keuangan Dan Literasi Keuangan Terhadap Kinerja UMKM - Dwi Saraswati; Yunita Sari Rioni; Ikhah Malikhah; Nura Amalia Afan (JURNAL AKUNTANSI AUDIT DAN PERPAJAKAN INDONESIA (JAAPI), 2024)
This study aims to analyze the influence of financial inclusion and financial literacy on the performance of MSMEs in Kota Pari Village. In this study, the researcher also measured the level of financial inclusion and financial literacy in MSMEs in Pari City Village. The research sample is the owners and managers consisting of 40 MSMEs in Kota Pari Village, Pantai Cermin District. This study uses a quantitative method. The data collection method uses a non-probability sampling technique using a questionnaire. This study uses the multiple linear regression analysis method. The results of this study show that there is a simultaneous influence between financial inclusion and financial literacy on the performance of MSMEs. And partially, the financial inclusion variable showed a percentage of 13.9% and the remaining 86.1% was explained by other variables. The level of financial inclusion and financial literacy of MSMEs in Kota Pari Village, Pantai Cermin District is still relatively low because it is <60%, namely only 58% and 37%.